BIODEGRADABILITY OF NANOCOMPOSITE MADE FROM PVA, ZnO NANOPARTICLES AND STEARIC ACID - Bayu Meindrawan; Vega Yoesepa Pamela (Food ScienTech Journal, 2019)
Nanocomposite film has been developed from PVA polymer added with ZnO nanoparticle and stearic acid to enhance its performance. Preparation of nanocomposite film was using the optimum film formulation with ZnO nanoparticle and Stearic acid composition 3.4% (w/w PVA) and 6.6% (w/w PVA), respectively. The biodegradability of the resulting film was evaluate using soil burial test and statistically analyze using t-test. The result show that the rate degradation of optimum nanocomposite film (1.3785 %/day) was not significantly difference (p>0.05) compare with control (1.4885 %/day).